PUBLIC PROCUREMENT, EMPLOYEE COMPETENCE AND STRATEGIC IMPLEMENTATION ON SERVICE DELIVERY - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
The study focused on Public procurement, Employee competence and Strategic implementation influence service delivery in the Ministry of Electricity, Dams, and Irrigation & Water Resources-the Republic of South Sudan. It assessed how Public procurement, Employee competence and Strategic implementation influence service delivery. The objectives of the study were to; examine the relationship between Public procurement and Service delivery; between Public procurement, Employee competence and Service delivery; between Public procurement, Strategic implementation and Service delivery, between accountability, corporate governance and financial reporting and the factor structure of Public procurement, Employee competence, Strategic implementation and Service delivery.The major findings of the study were that there is a significant positive correlation between; procurement and service delivery at values (r = .204*, p = 0.001) public procurement, employee competence and service delivery at values  (r = 1, .818**, .204** and p-values = 0.000, 0.000 and 0.001), procurement, strategic implementation and service delivery at values (r = .087**, .204** and p-values = 0.000, 0.000 and 0.001) and factor structure of Public procurement, Employee competence, Strategic implementation and Service delivery at values (R Square = .984, Adjusted R Square = .983, F = 5.505E3 and Sig. = .000a).The study recommends that there is need for the Ministry of Electricity, Dams, Irrigation & Water Resources to lay effective procurement management systems so that effective service delivery is achieved, there is need for them to improve on the competencies of their employees by giving them other trainings and incentives that will motivate them to work hard and carry out the monitoring, evaluation and control of other employees they work with to ensure effective service delivery, the government should put procurement management measures and implementation strategies to ensure funds are used for the right purpose in the ministry and research and assessment appraisals are recommended in order to get the real picture of service delivery in the ministry